Potential of baroma rice as anti-cancer food candidate via cell cycle arrest and apoptosis - Pranatami, Dwimei Ayudewandari; Akmalia, Hafidha Asni (Universitas Gadjah Mada, 2025)
Cancer is a condition where the body's cells continue to divide without control. Often, this cancer is detected when it has entered an advanced stage, making it difficult to treat. Rice is a staple food widely used by more than half of Indonesia's population. The position of rice, which is a staple food, can be used as a prospective treatment to overcome the increasing number of cancer cases, especially in cases of colon cancer. Rice is reported to have many beneficial chemical contents. In cytotoxicity testing using WiDr colon cancer cells, the IC50 of the ethanolic extract of baroma rice is 316.01µg/ml. Stovetop cooked baroma rice showed an IC50 value of 672 µg/ml, while magic com cooked rice showed an IC50 value of 1232 µg/ml. Raw and stove-cooked baroma rice extracts are not strong enough to trigger apoptosis in cancer cells and can arrest the cell cycle at the G1 stage. This research shows that baroma rice extract has cytotoxic properties against WiDr colon cancer cells and various other evidence regarding the advantages of baroma rice. It is hoped that this rice can become a food that can prevent colon cancer.